Queues with Dynamic Priority Discipline - Jackson, James R. (Management Science, 1961)
A report on the writer's computer simulation studies of queues in which service order is governed by due-date-like priorities. The main results are in the form of conjectures about the upper tails of the waiting-time distributions. Pertinent mathematical research is mentioned.